Postoperative Endoscopic Recurrence on the Neoterminal Ileum But Not on the Anastomosis Is Mainly Driving Long-Term Outcomes in Crohn's Disease. (22nd July 2020) - Hammoudi, Nassim; Auzolle, Claire; Tran Minh, My-Linh; Boschetti, Gilles; Bezault, Madeleine; Buisson, Anthony; Pariente, Benjamin; Treton, Xavier; Seksik, Philippe; Fumery, Mathurin; Le Bourhis, Lionel; Nancey, Stéphane; et al.
Abstract : INTRODUCTION: Early ileocolonoscopy within the first year after surgery is the gold standard to evaluate recurrence after ileocolonic resection for Crohn's disease (CD). The aim of the study was to evaluate the association between the presence and severity of anastomotic and ileal lesions at early postoperative ileocolonoscopy and long-term outcomes. METHODS: The REMIND group conducted a prospective multicenter study. Patients operated for ileal or ileocolonic CD were included. An ileocolonoscopy was performed 6 months after surgery. An endoscopic score describing separately the anastomotic and ileal lesions was built. Clinical relapse was defined by the CD-related symptoms, confirmed by imaging, endoscopy or therapeutic intensification; CD-related complications; or subsequent surgery. RESULTS: Among 225 included patients, long-term follow-up was available in 193 (median follow-up: 3.82 years [interquartile range: 2.56–5.41]). Median clinical recurrence-free survival was 47.6 months. Clinical recurrence-free survival was significantly shorter in patients with ileal lesions at early postoperative endoscopy whatever their severity was (I(1) or I(2, 3, 4)) as compared to patients without ileal lesions (I(0)) (I(0) vs I(2, 3, 4): P = 0.0003; I(0) vs I(1): P = 0.0008 and I(1) vs I(2, 3, 4): P = 0.43). Patients with exclusively ileal lesions (A(0)I(1, 2, 3, 4)) had poorer clinical long-term outcomes than patients with exclusively anastomotic lesions (A(1, 2, 3)I(0)) ( P = 0.009). DISCUSSION: A score describing separately the anastomotic and ileal lesions might be more appropriate to define postoperative endoscopic recurrence. Our data suggest that patients with ileal lesions, including mild ones (I(1)), could beneficiate from treatment step-up to improve long-term outcomes.